Speaking of speaking : marking direct discourse in the Hebrew Bible - Meier, Samuel A. (Supplements to Vetus Testamentum, 1992)
Direct speech appears on nearly every page of the Hebrew Bible, and the large number of publications on direct discourse in the Bible highlights the importance of the subject for biblical studies. However, thus far only isolated aspects of the various problems that direct discourse presents have received attention. Studies of individual verbs introducing direct discourse, such as \'answer\', \'speak\', \'say\', and others are necessarily atomistic, even though appropriate in their own right. Other markers of direct discourse, such as \'Thus said Yahweh\', or \'oracle of Yahweh\', tend to be treated as theological constructs isolated from the larger issues of direct discourse marking in general. Speaking of Speaking aims to enrich the reading of the biblical text by offering a coordinated analysis of all such markers, not only in order to consolidate a considerable body of work that is often overlooked by scholars, but also to move further toward a synthesis that can permit informed generalizations not possible at the present time. The comprehensive index facilitates the use of this book as a valuable reference tool. The exegetical, literary, and theological findings of this book will be of great significance for all levels of research in biblical studies.